Potentials and limitations for the use of accessibility measures for national transport policy goals in freight transport and logistics: Evidence from Västra Götaland County, Sweden - Anders Larsson; Jerry Olsson (REGION, 2017)
In Swedish national transport policy is freight transport regarded as a major facilitator for economic development on all geographical levels. At the same time it is noted that methods and data on business location and transportation is not adequate in order to follow-up transport policy objectives. This paper reports on a pilot study on the potential to develop accessibility measures to support and follow up policy objectives in Swedish context. The concept of accessibility and its practical use in concrete measures is discussed and problematized. A number of practical examples from Region Västra Götaland are used as illustrations. In terms of results the study identifies a number of potentials and limitations of using accessibility measures for freight transport issues. The usefulness is mainly driven by the integration capability of transport and land-use. This opens up for more complex questions and measures and thus supports the integration between planning specialisations. Limitations are to a large extent related to data availability and quality and to the degree of which models are possible to communicate to non-experts. The concluding discussion highlights how the policy and governance context is key in understanding how to best utilise the potential strengths of the accessibility concept and measures.
Keywords: 330; accessibility; freight transport; logistics facilities; transport policy